Kant and the spirit of critique - Sallis, John, 1938- (The collected writings of John Sallis, 2020)
This volume of the Collected Writings of John Sallis presents his lecture courses on Kant. Each course was devoted respectively to one of Kant's three Critiques, and so the book as a whole treats the entirety of the Kantian critical project. Sallis displays here, as he does in all his lecture courses, an uncanny ability to open up dense philosophical texts. The matters Kant deals with'in theoretical, practical, and aesthetic philosophy'are difficult in themselves, and Kant's writings might at times seem so convoluted as to magnify the difficulty. Sallis patiently and successfully lays out the issues and the critical approach to them, such that the reader is led step by step into the very core of Kant's spirit of critique. This volume makes Kant accessible to students, while the most advanced scholars will also profit from it.